3-D realistic simulations over a Flatfish shaped AUV submitted to ocean currents. (September 2019) - da Silva Costa, G.; Almeida, M.P.; de Melo Filho, A.R.V.; da Cunha Lima, A.T.; da Cunha Lima, I.C.
Abstract: This work aims to analyze the torque effects produced by the hull-wake interaction on the maneuverability of a flatfish-shaped AUV, by 3-D realistic scale computational simulations. On account of the inertia, the AUV provides a self-averaging mechanism that erases the high frequency components. Following this line, we processed a high frequency filter on the torques time series. We concluded that the flatfish shape has an excellent capacity of maneuverability under low velocities, showed by its tiny torque variations over time as the inlet speed decreases. We also observe that the pitch component has high torque oscillations over time with drift (also called yaw) angles, showing a significant increment of amplitudes when this angle becomes 10°. This represents an important concern about flatfish maneuverability while, on the other hand, the roll component has shown the lowest oscillations among the three rotational degrees of freedom. The yaw component increases moderately with an increase in attack yaw angles. The description above, especially for low speeds, indicates that the flatfish-shaped AUV presents suitable conditions for missions executing scanning and filming tasks that require good stability and controllable maneuverability.